Pengaruh Media Sosial Terhadap Identitas Diri Remaja - Putri, Melisabrona; fitri, wanda; Nasril, Nasril; elvina, siska novra (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2023)
This study aims to determine the effect of social media on adolescent self-identity. Social media for teenagers is one of the places that can help find their identity. In addition, communication through social media is not too burdensome and scary for teenagers because it can change their character easily on social media. The self-character displayed by teenagers on social media is an ideal self that is sometimes different from their actual self in everyday life. The research method is quantitative using Logistic Linear Regression Analysis. The population is teenagers in Nagari Ganggo Mudiak Kec. Bonjol, Pasaman Regency, totaling 96 people. The sampling technique uses Total Sampling, which makes all members of the population used as samples. Data were collected using a questionnaire with a Likert Scale model, and processed using the SPSS version 20.0 program. The results of the study show that: 1) The category of adolescent social media users uses several types of social media simultaneously, 42.7% of adolescents use Facebook, YouTube, WhatsApp, and Instagram more often. 2) The category of adolescent self-identity as much as 57.3% have a high level of self-identity. 3) Social media has an effect on adolescent self-identity, this is shown from the results of logistic linear regression between social media variables and self-identity variables, there is an R-Square value of 0.194 which means that adolescent self-identity is influenced by social media. Keywords: Social media, adolescent self-identity.